Nilai Patriotisme Dalam Kearifan Lokal Suku Sasak (Resepsi Ekosufism Masyarakat Dusun Sade, Kecamatan Pujut, Kabupaten Lombok Tengah) - Abd. Razzak; Ulya Hilalatul Hasbi; Muh. Azkar; Muhammad Habiburrahman (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Modern humans are experiencing many different acute crises. According to Nasr, the great ecological crisis is the result of human ambition to exploit nature. In other words, the main cause of the ecological crisis is a scientific lifestyle that does not consider modern science as a means to understand nature. Instead, it is considered a philosophy that, as a whole, reduces all reality to its material parts and does not accept unscientific worldviews. The Sasak tribe (read: Lombok) has diverse local wisdom and is rich in meaning. One of the villages that practices both consciously and unconsciously about eco-sufism is the Sade hamlet, Rambitan village, Pujut District, Central Lombok. This paper will look at how the value of patriotism in local wisdom in ecosufism in the Sade hamlet. The value of patriotism is a value that teaches love for the homeland, courage, willingness to sacrifice, sincerity, and never give up. This paper examines and analyzes the eco-sufism of the Sade hamlet with environmental ethics from the perspective of Seyeed Hosesin Nasr. The concept of environmental ethics put forward by Nasr is rooted in two concepts. First on the concept of unity (tawhid) and second the concept of man. The universe is the manifestation of God. Man as in the Qur'an plays the role of servant ('abd) as well as caliph (khalifah) of God. These two words are the key to understanding man. As a result, the Sade hamlet has several traditions and cultures that are full of meaning, including in terms of house architecture and awik-awik.